Implementasi Cloning Data Menggunakan Aplikasi EaseUS Partition Master Dengan Menerapkan Metode Workflow - Yennimar -; Julfan Farman Zebua; Wikesyah Putri Sitorus; Kristina Ginting; Yans Y.M.P. Situmorang (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
Data cloning implementation is an essential process in information technology to duplicate content from one storage device to another. EaseUS Partition Master is a popular software used to implement this data cloning process. This abstract discusses the implementation of data cloning using EaseUS Partition Master. Data cloning is an efficient way to duplicate the entire contents of one hard drive or partition to another storage device. EaseUS Partition Master offers extensive capabilities in performing data cloning with various features that can facilitate users in carrying out the process. One of the most commonly used cloning features is